Księgi Metamorphoseon by W. Otwinowski as the Source for Russian Translations of Ovid’s Metamorphoses in Early 18th Century: Nomination of Sanctuaries - Matveenko, Ekaterina (Slavistica Vilnensis, 2021)
The article examines the translation of lexemes nominating shrines in Polish Ovid’s Metamorphoses adaptation Księgi Metamorphoseon, to jest, Przemian od Publiusa Owidiusza Nasona Wierszami opisane made by Walerian Otwinowski in 1638. From this Polish verse translation in early 18th century was made both Russian translations of Metamorphoses. Thus the results of present study can be considered also as starting point for further examination of Russian translations. It is determined that in Otwinowski’s version lexeme kościół was chosen as a unified neutral equivalent for some different Latin nominations of pagan sanctuaries. Comparison with another Polish translation of Metamorphoses, Jakob Żebrowski’s Metamorphoseon, to jest Przeobrażenia ksiąg piętnaście (1636), shows that Otwinowski’s decision to translate different Latin lexical equivalents by unified lexical item is a distinctive feature of his translation. For further study in translation techniques in both Russian translations it is important that the Polish origin (Otwinowski’s translation) itself doesn’t represent a field for a variety of translation correspondences within considered lexemes.
Keywords: Ovid’s Metamorphoses; translation techniques; Polish-Latin translations; nomination of sanctuaries; Walerian Otwinowski